CHEMICAL COMPOSITION OF BRACHYURAN CRABS FROM VARIOUS ENVIRONMENTS - JEYALAKSHMI KALA, K.L; M. CHANDRAN (International Journal of Pharma and Bio Sciences, 2014)
Crabs are a good source of protein, carbohydrates and various minerals. Therefore, determining of the proximate and mineral elements of crab species has a great importance due to the good effect on human health. In the present study proximate and minerals composition of the crabs collected from the marine, estuarine, freshwater and terrestrial environments were analysed. The study reveals the higher protein content was observed in the marine crabs Portunus pelagicus (23.23±0.22) and lowest protein level (13.23±0.02) was recorded in Cardisoma carnifex crabs. In the body meat minimum carbohydrate content (1.1±0.02%) was recorded in Barytelphusa cunicularis crabs and maximum (1.32±0.01%) value were recorded in the land crab C. carnifex. Particularly, marine and estuarine crabs posses higher protein content than the land and fresh water crabs. However, the findings of minerals of calcium, magnesium, sodium and potassium composition of estuarine and marine crabs particularly is more but the content of iron and copper content was high fresh water and terrestrial crab species. It can then be inferred that the crabs could be employed as a supplement of protein and mineral matter so as to balance human nutrition. Hence the consumption of marine crabs would help to prevent nutritional deficiencies in the future. It could be safely presumed that P. pelagicus is a good source of protein and recommended as an ideal food item.